2003
DOI: 10.1590/s0021-75572003000100011
|View full text |Cite
|
Sign up to set email alerts
|

Inquérito sobre a qualidade de vida relacionada à saúde em crianças e adolescentes portadores de artrites idiopáticas juvenis

Abstract: The responsiveness of two health related quality of life tools indicates their relative sensitivity for assessing clinical improvement during active treatment in Juvenile Idiopathic Arthritis patients.\par

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
2
0
10
Order By: Relevance
“…[11][12][13] Quality of life of rheumatic patients -Carvalho MF et al The result shown by the CHQ of patients with rheumatic fever revealed median values similar to those found in other studies involving children with chronic diseases such as: attention deficit disorder, asthma, epilepsy, psychiatric diseases, juvenile idiopathic arthritis, among others. 3,5,7,[9][10][11][12] When analyzing the results of healthy Brazilian children on the CHQ, we found that they had lower scores on CHANGE, followed by alterations on BE and PE. 6 Some studies have used other generic questionnaires, such as the Peds QL TM , which was administered to children with chronic diseases and their guardians, and these studies have found discordant results regarding the quality of life of the children investigated.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[11][12][13] Quality of life of rheumatic patients -Carvalho MF et al The result shown by the CHQ of patients with rheumatic fever revealed median values similar to those found in other studies involving children with chronic diseases such as: attention deficit disorder, asthma, epilepsy, psychiatric diseases, juvenile idiopathic arthritis, among others. 3,5,7,[9][10][11][12] When analyzing the results of healthy Brazilian children on the CHQ, we found that they had lower scores on CHANGE, followed by alterations on BE and PE. 6 Some studies have used other generic questionnaires, such as the Peds QL TM , which was administered to children with chronic diseases and their guardians, and these studies have found discordant results regarding the quality of life of the children investigated.…”
Section: Discussionmentioning
confidence: 86%
“…The scores revealed in these groups are presented in Table 1, as well as the scores resulting from the administration of the questionnaire to healthy children in the study that validated the instrument in Brazil. [5][6][7][8][9][10] The objective of the present study is to assess the quality of life of patients with rheumatic fever receiving outpatient treatment at two public hospitals that are centers of excellence for the treatment of rheumatic fever in the municipality of Rio de Janeiro (RJ).…”
Section: Introductionmentioning
confidence: 99%
“…O resultado apresentado no CHQ de pacientes com febre reumática mostrou medianas próximas às observadas em outros estudos de crianças com doenças crônicas tais como: distúrbio de déficit de atenção, asma, epilepsia, doenças psiquiátricas, artrite idiopática juvenil e outras 3,5,7,[9][10][11][12] . Ao observarmos os resultados do CHQ em crianças brasileiras saudáveis, verificamos que elas tiveram pior desempenho no item CHANGE, seguida por alteração no BE e PE 6 .…”
Section: Discussionunclassified
“…O CHQ foi construído utilizando algumas doenças crônicas como modelos clínicos, e os escores obtidos nesses grupos são apresentados na Tabela 1, assim como os obtidos com a aplicação do questionário em crianças saudáveis no estudo de validação do instrumento no Brasil [5][6][7][8][9][10] .…”
Section: Introductionunclassified
“…Calidad de Vida infantil ha sido definida como un concepto subjetivo y multimensional que incluye la capacidad funcional y la interacción social del niño y su familia (BRASIL, FERRIANI, MACHADO, 2003). Otros autores, coinciden en su multidimensionalidad y señalan que abarca varios dominios centrales, como condiciones materiales, condición física y habilidades funcionales, interacción social y bienestar emocional (WHITE-KONING M, et al, 2005).…”
Section: Indroducciónunclassified